Generation of nitric oxide in roots of Pisum sativum, Triticum aestivum and Petroselinum crispum plants under osmotic and drought stress - Kolbert Zsuzsanna (Acta biologica Szegediensis, 2005)
The concentration-, time- and tissue-dependent generation of nitric oxide (NO) was investigated in roots of Pisum sativum L. and Triticum aestivum L.. under osmotic stress, as well as in Petroselinum crispum L. under drought stress. Osmotic stress for pea and wheat was induced by polyethylene glycol (PEG) treatments in nutrient solution, while drought stress was caused by withdrawal of watering of soil-grown parsley. NO was detected by the NO-specific fluorescent dye, 4,5-diaminofluorescein-diacetate (DAF-2DA), using Zeiss Axiowert 200 M type fluorescent microscope. Changes in nitrate reductase activity was determined in the same series of treatments. Our results show that NO generation was proportional to the osmotic concentration of PEG both in pea and wheat roots and to the severity of drought in parsley root. The sites of NO production were in the regions of meristemic and elongation zones, and in case of wheat, root cap was also involved. In parsley root, the exodermis and the central cylinder showed the most intensive NO accumulation. In wheat and pea, time course revealed a fast transient (several hours) and a slow permanent increase in NO production. It is suggested that the fast kinetics may be due to non-enzymatic, while the constant increase was caused by enzymatic reactions. In parsley, long term experiments were carried out including the regeneration process after rewatering. It is concluded that NO plays a role as signaling molecule under osmotic and drought stress conditions.